Influence of temperature on the electrical resistivity of concrete and kinect corrosion of reinforcement - Chaves Chiaradia, Lucas; Rosa Almeida, Fernando do Couto; Paulino Aguilar, Maria Teresa; Pazini Figueiredo, Enio José (Revista ALCONPAT, 2024)
The work evaluated the influence of temperature on the concrete electrical resistivity measurements and corrosion kinetics in reinforced concrete structures subjected to chlorides. The concretes were mechanically characterized at 28 and 90 days. After 204 days, the specimens were subjected to temperature cycles ranging from 55 °C to -5 °C. The results indicated that the corrosion kinetics and electrical resistivity varied with the temperature changes. At higher temperatures, dosages contaminated with Cl- showed a high probability of corrosion and a decrease in electrical resistivity values, however, at negative temperature, the probability of corrosion was insignificant and the electrical resistivity values were the highest.